Effects of Exercise During Pregnancy on Postpartum Depression: A Systematic Review of Meta-Analyses - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Postpartum depression (PPD) is a public health issue. Exercise is a nonpharmacologic alternative to deal with PPD. This study conducted a systematic review of previous meta-analyses and an exploratory pooled analysis regarding the effects of exercise on depressive symptoms among women during the postpartum period. We searched for previous meta-analyses of randomised controlled trials on PubMed, Web of Science and Scopus, date of inception to 31 May 2021. The methodological quality was assessed using the Assessment of Multiple Systematic Reviews 2 (AMSTAR2) instrument. We pooled the standardised mean differences from the selected studies. Of the 52 records screened, five were included. The results revealed a significant moderate effect of exercise on depressive symptoms among women during the postpartum period (SMD = −0.53; 95% CI: −0.80 to −0.27, p < 0.001). The pooled effect of the five meta-analyses established that exercise had a significant, small effect on depressive symptoms (SMD = −0.41; 95% CI: −0.50 to −0.32, p < 0.001). Our study indicates that exercise is effective in reducing PPD symptoms. Compared with traditional control approaches (psychosocial and psychological interventions), exercise seems have a superior effect on PPD symptoms. The implications of the present synthesis of past meta-analytical findings to guide health policies and research are discussed. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.